By using property of logarithms, We get the answer
In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex] = In (x + 1) + In (x -1) - 7 In x
Given,
In the question:
The equation is :
In [tex]\frac{x^{2} -1}{x^7}[/tex] , x > 1
To solve by using by using property of logarithms to expand the expression as a sum, difference, and / or constant multiple of logarithms.
Now, According to the question:
We know that:
The property of logarithms is:
[tex]log_{a}{\frac{m}{n} } = log_{a}m - log_{a}n[/tex]
The given equation is :
In [tex]\frac{x^{2} -1}{x^7}[/tex] , x > 1
In [tex]\frac{x^{2} -1}{x^7}[/tex] = In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex]
Again, Using the another property of logarithms.
[tex]log_am^x = nlog_am[/tex] {x∈ R}
In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex] = In [tex](x^2 -1)[/tex] - 7 In x
In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex] = In [ (x + 1)(x - 1)] - 7In x
In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex] = In (x + 1) + In (x -1) - 7 In x
{Log (mn) = [tex]log_{a}m - log_{a}n[/tex]}
Hence, By using property of logarithms, We get the answer
In [tex](x^2 -1)[/tex] - In [tex]x^7[/tex] = In (x + 1) + In (x -1) - 7 In x
Learn more about Logarithms at:
https://brainly.com/question/27389970
#SPJ4